ANALISIS KEKUATAN TIANG PANCANG SPUN PILE PADA ABUTMENT JEMBATAN ANJIR SERAPAT KM. 11 (Strength Analysis Of Spun Pile At Anjir Serapat Bridge Abutment Km. 11) - Miming Virganinda; Anri Lamhot P. Lumban Gaol (Fakultas Teknik Universitas Kristen Palangka Raya, 2021)
A bridge is a building built over a railroad, river or road so that people or vehicles can cross from one side to the other. Bridge buildings in general must be strong to withstand heavy vehicles passing on it, strong to withstand strong winds from the side withstand the vibrations caused by the earthquake. The pile foundation is part of the structure that is used to receive and transfer (transmit) loads from the superstructure to the supporting soil which is located at a certain depth. The pillars are long and slender which transfers the load to deeper ground. The main materials of the poles are iron and concrete.The understructure of this bridge consists of abutments and foundations, both of which have an important role in supporting the bridge structure. The planned abutment dimensions are 3.876 m high, with a pile cap width of 3.80 m and a pile cap length of 6 m. The establishment of a bridge is also due to the strong foundation that supports the bridge. The type of foundation used under the existing abutments is pile foundation with a diameter of 500 mm and a depth of ±35 m and a pile cap thickness of 1 m. Based on the SPT test data, sandy soil conditions with an N value 60. Keywords: Bridges, Spun Pile, Piles, Abutments, Concrete.